2008
DOI: 10.1002/anie.200704488
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Gas and Vapor Sensors

Abstract: Carbon nanotubes have aroused great interest since their discovery in 1991. Because of the vast potential of these materials, researchers from diverse disciplines have come together to further develop our understanding of the fundamental properties governing their electronic structure and susceptibility towards chemical reaction. Carbon nanotubes show extreme sensitivity towards changes in their local chemical environment that stems from the susceptibility of their electronic structure to interacting molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
603
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(610 citation statements)
references
References 218 publications
(177 reference statements)
6
603
0
1
Order By: Relevance
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] This high affinity for CO over O 2 of hemoglobin and myoglobin is the underlying mechanism of carbon monoxide poisoning in mammals. [8,9] Although detectors for CO are available, there remains a need for massively [16,17] Theoretical and experimental reports have suggested that CO does not engage in charge transfer with pristine SWCNTs, [18][19][20] indicating the a chemical reactive interface is necessary. Conductivity-based CO detection has been reported for carboxylate-containing, [19] deformed, [21] or doped SWCNTs, [22] as well as SWCNTs dispersed in polymers [23] or decorated with metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Sensors without iron porphyrin-both pristine (not shown) and functionalized (black curve) SWCNTsshowed negligible responses to CO, which was consistent with the previous reports. [18][19][20]27] Sensors with iron porphyrin showed dosimetric responses indicating irreversibility over the experimental time frame. Pristine SWCNTs (lacking the 4-pyridyl anchor group) when treated with Fe(tpp)ClO 4 (green curve) showed a modest response (−0.57 ± 0.09%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the great progress achieved in this field, CNTs have been used to synthesize not only various polymer/CNTs composites [4][5][6][7][8] but also various CNTs/metal oxide hybrids [9][10][11][12][13], where CNTs can serve as high-performance supporting materials. The decoration of CNTs with metal oxide nanoparticles can give them new properties and potentials for various applications [14][15][16][17][18]. Among them, the CNTs coated Fe 3 O 4 nanoparticles have attracted much increasing interest because of the excellent magnetic and biocompatible properties, which make them to be applied in electrochemical biosensing [19], biomanipulation [20], targeted drug delivery [21] and contaminant treatment [22].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important applications of such gas sensors involves the ability to monitor the leakage of nitrogen-based gases such as ammonia (NH 3 ) and nitrogen dioxide (NO 2 ) in the air because these chemicals adversely affect human and environmental health [5]. NH 3 is primarily a concern in areas of high agricultural activity because it is a natural waste product of livestock whereas it can also be a product of industrial sources, including the manufacturing of basic chemicals, metals, and textile products as well as automotive emissions.…”
mentioning
confidence: 99%